2012
DOI: 10.1590/s0100-39842012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Dopplerfluxometria de artérias oftálmicas e avaliação da função endotelial nas formas precoce e tardia da pré-eclâmpsia

Abstract: Objective: To identify possible differences between endothelial dysfunction evaluated by brachial artery flow-mediated dilation and central hyperperfusion evaluated by dopplerfluxometry of ophthalmic artery in women with early-and lateonset preeclampsia. Materials and Methods: Flow-mediated dilation testing and dopplerfluxometry of ophthalmic artery were performed in 81 patients (26 with early preeclampsia, 30 with late preeclampsia, and 25 normotensive pregnant women -control group). Results: As compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Brandão et al . found the RI to be lower among 26 patients with early‐onset PE and in 30 patients with late‐onset PE compared with 28 healthy controls in a cross‐sectional study during the third trimester.…”
Section: Discussionmentioning
confidence: 90%
“…Brandão et al . found the RI to be lower among 26 patients with early‐onset PE and in 30 patients with late‐onset PE compared with 28 healthy controls in a cross‐sectional study during the third trimester.…”
Section: Discussionmentioning
confidence: 90%
“…Possible explanations for this fact are based on the principle that the central hyperflow may occur after the blood pressure increase and glomerular endothelial injury, so that the clinical manifestations of PE precede the decrease in OARI in affected patients. A study carried out in our center has demonstrated a significant decrease in OARI at the moment when the PE was diagnosed 24 , in both its early and late forms. New studies that evaluate the behavior of OARI at the later gestational ages, such as the beginning of the third trimester, could validate the In conclusion, our results demonstrate that impaired placental perfusion and systemic endothelial dysfunction temporarily precede the clinical manifestations of PE, which does not occur with central hyperflow.…”
Section: Discussionmentioning
confidence: 89%
“…Endothelial injury evaluated by FMD is well established in patients with diagnosis of PE, either in cases of early or late presentation (15) . In a study developed by Savvidou et al, the methods association was more effective in the identification of the patients at risk for developing PE and restricted intrauterine growth than Doppler flowmetry of uterine arteries alone (16) .…”
Section: Discussionmentioning
confidence: 99%